Self-Sustaining Systems: First Workshop, S3 2008 Potsdam, Germany, May 15-16, 2008 Revised Selected Papers - Hutchison, David; Kanade, Takeo; Kittler, Josef (Lecture notes in computer science, 2008)
The Workshop on Self-sustaining Systems (S3) is a forum for the discussion of topics relating to computer systems and languages that are able to bootstrap, implement, modify, and maintain themselves. One property of these systems is that their implementation is based onsmall but powerfulabstractions;examples include (amongst others) Squeak/Smalltalk, COLA, Klein/Self, PyPy/Python, Rubinius/Ruby,andLisp.Suchsystemsaretheenginesoftheirownreplacement, giving researchers and developers great power to experiment with, and explore future directions from within, their own small language kernels. S3 took place on May 15-16, 2008 at the Hasso-Plattner-Institute (HPI) in Potsdam, Germany. It was an exciting opportunity for researchers and prac- tioners interested in self-sustaining systems to meet and share their knowledge, experience, and ideas for future research and development. S3 provided an - portunity for a community to gather and discuss the need for self-sustainability in software systems, and to share and explore thoughts on why such systems are needed and how they can be created and deployed. Analogies were made, for example, with evolutionary cycles, and with urban design and the subsequent inevitable socially-driven change. TheS3participantsleftwithagreatersenseofcommunityandanenthusiasm for probing more deeply into this subject. We see the need for self-sustaining systems becoming critical not only to the developer's community, but to e- users in business, academia, learning and play, and so we hope that this S3 workshop will become the ?rst of many.